Persistent Hydrocephalus and Activated Microglia Drive the Spatial Memory Decline After Intraventricular Hemorrhage in Rodents. (1st September 2019) - Kamal, Kimia; Binyamin, Tamar; Keiter, Janet A; Vergara, Audrey R; Izadi, Ali; Ondek, Katelynn; Berman, Robert; Sharp, Frank; Gurkoff, Gene G; Waldau, Ben
Abstract: INTRODUCTION: Intraventricular hemorrhage (IVH) can result in significant cognitive deficits and spatial memory impairments that can prevent over half of IVH patients from returning to work after recovery. The mechanism of this memory decline, however, is incompletely understood. METHODS: To understand the role of mechanical trauma caused by rapid ventricular expansion vs the presence of blood components, such as thrombin, in IVH deficits, we developed a rodent model of IVH by injecting 200 μL of autologous arterial blood into the animals' ventricles. The IVH animals' memories were then assessed along with sham (no injection), vehicle control (200 μL aCSF), and intraventricular thrombin (IVT) (20 U thrombin in 5 μL aCSF) animals using Morris water maze. RESULTS: The IVH group performed worse on this spatial memory task compared to all other groups, indicating that ventricular expansion and presence of blood components both contribute to memory deficits. Based on magnetic resonance imaging (MRI) results, the IVH group was also the only group that developed persistent hydrocephalus. Contrary to our hypothesis that the cognitive deficits of IVH are due to decreased hippocampal neurogenesis, we did not find any statistical difference in the numbers of dentate gyrus progenitor cells (labeled with BrdU and DCX) or neurons (labeled with NeuN) between the different groups. The number of microglia (labeled with Iba1) was also compared among the groups and found to be not statistically different. The microglia in IVH and vehicle control animals, however, were found to have significantly lower fractal dimension ( P  < .001) and higher lacunarity ( P  < .001) numbers compared to those of sham animals, indicating a more activated state, likely caused by the mechanical trauma. CONCLUSION: Based on our results, persistent hydrocephalus microglial activation seem to be the drivers of spatial memory deficit after IVH.